Study guides

☆☆

Q: How do you simplify 2x plus 3 x 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3 * x + 4 + 2xMDAS rule:3x + 4 + 2x5x + 4

X = 0.8

(4x + 12)/(8x - 4y) = [4(x) + 4(3)]/(4(2)(x) - 4y] = 4(x + 3)/4(2x - y) = (x+ 3)/(2x - y)

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.

x= -3

Related questions

3 * x + 4 + 2xMDAS rule:3x + 4 + 2x5x + 4

OK, SO 15x-3 = 2x+1 15x - 3 + 3 = 2x + 1 + 3 (add three to each side) 15x=2x+4 (simplIfy) 15x-2x=2x-2x+4 (subtract 2x from each side) 13x=4 (simplify) (13x/13)=(4/13) (divide each side by 13) x≈0.30769231

If there are no equals you can simplify this by collecting all the x values together and use the addition property of signed numbers. 2x+4x-5x+x=2x; 4+3=7. 2x+7 is the simplified statement.

Factor it out: (x+2) squared

x - 3x + 4 = 3 - 9 simplify -2x + 4 = -6 -4 -4 -2x = -10 /-2 /-2 x = 5

2

By collecting like terms: 8z+4-2x

2x3x-4= -24

X = 0.8

(4x + 12)/(8x - 4y) = [4(x) + 4(3)]/(4(2)(x) - 4y] = 4(x + 3)/4(2x - y) = (x+ 3)/(2x - y)

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

People also asked